2012
DOI: 10.1371/journal.pone.0047667
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Characteristics of Patients with Urinary Tract Hydatid Disease

Abstract: BackgroundHuman cystic echinococcosis (CE) is caused by flatworm larvae of Echinococcus granulosus and is endemic in many parts of the world. In humans, CE cysts primarily affect the liver and pulmonary system, but can also affect the renal system. However, the clinical manifestations of renal CE can be subtle, so healthcare professionals often overlook renal CE in differential diagnosis. In this study, we examined the clinical and demographic characteristics of patients with urinary tract CE and analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In our case, the cyst was iden- tified incidentally. It has been reported that it settles in the left kidney more often than the right, and it is thought that this situation may be related to the fact that the left renal artery is shorter than the right renal artery (4,5). In our case, the lesion was located in the right kidney.…”
Section: Discussionmentioning
confidence: 46%
“…In our case, the cyst was iden- tified incidentally. It has been reported that it settles in the left kidney more often than the right, and it is thought that this situation may be related to the fact that the left renal artery is shorter than the right renal artery (4,5). In our case, the lesion was located in the right kidney.…”
Section: Discussionmentioning
confidence: 46%
“…It is obvious from this study and many authors' results which showed different data of human cystic Echinococcus infection that CE is still a public health problem and predominantly in many countries (Schantz 1991;Siracusano et al 2008;Huang and Zheng 2012). Therefore, clinicians and health authorities should pay greater attention to CE and should make additional efforts to decrease or even eliminate this disease in the future.…”
Section: Discussionmentioning
confidence: 70%
“…The patient had a shorter clinical course compared to our patient [ 18 ]. A case series of 11 patients with renal hydatid cyst was reported by Zargar et al [ 19 ]. Among these patients, only two patients were older than 60 years of age.…”
Section: Discussionmentioning
confidence: 99%